2013
DOI: 10.1002/jsfa.6137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water-saving irrigation regime on whole-plant yield and nutritive value of maize hybrids

Abstract: The lack of differences on yield and nutritive value in tested maize hybrids grown under different water supply suggests the water-saving regime could be suitable for an optimal use of available water in maize management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…Adoption of more technically efficient irrigation infrastructure would help offset the crop water needs; each 10% reduction in PSIA would decrease irrigation depth by approximately 5.0%, when holding other factors constant (Figure 3b). These results are similar to earlier studies conducted on experimental fields Masoero et al 2013) and state-level data (McDonald and Girvetz 2013), which also suggested drier climate leads to additional irrigation use but that it can be partially counteracted by greater-efficiency irrigation technology. The county-level datasets used here not only confirm the past studies but also provide a broader-scale quantification.…”
Section: Discussionsupporting
confidence: 91%
“…Adoption of more technically efficient irrigation infrastructure would help offset the crop water needs; each 10% reduction in PSIA would decrease irrigation depth by approximately 5.0%, when holding other factors constant (Figure 3b). These results are similar to earlier studies conducted on experimental fields Masoero et al 2013) and state-level data (McDonald and Girvetz 2013), which also suggested drier climate leads to additional irrigation use but that it can be partially counteracted by greater-efficiency irrigation technology. The county-level datasets used here not only confirm the past studies but also provide a broader-scale quantification.…”
Section: Discussionsupporting
confidence: 91%
“…The limitation of this approach is that the measurement of starch degradation should be carried out over differing incubation times to assess rates of starch digestion, which is a laborious process and often results in variable estimates of starch digestion rate. Commonly, the evaluation of in vitro starch degradability is analyzed after a 6, 7, or 8 h incubation, even if shorter times (i.e., from 1 to 5 h) have been proposed . The type of rumen fluid used as inoculum can strongly influence the overall in vitro estimates of starch degradation especially if the rumen microflora have not been previously adapted to high starch diets .…”
Section: Methods To Evaluate Starch Digestion In Feed Grainsmentioning
confidence: 99%
“…In the present experiment, water supply throughout the CS cropping season was considerably lower than this level ranging between 231 and 572 mm among sites and years. Masoero et al [44] reported a lack of difference in CS yield and quality grown under different water supply. Inversely and contrary to our study, Gallo et al [45] reported a negative effect of water restriction on biomass yield and nutritive characteristics.…”
Section: Predicting Yield and Nutrient Concentrationsmentioning
confidence: 99%